PENERAPAN METODE ECONOMIC ORDER QUANTITY PADA PT NINDYA BETON SALATIGA - Dionisius Ricky Artha Kusuma, Bambang Widarno & Muhammad Rofiq Sunarko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
One method in inventory management is the EOQ method. EOQ method is toidentify orders to minimize the amount of inventory storage costs, purchase a rawmaterial with each purchase at minimum cost, and an order that minimizes totalinventory cost. So EOQ method can save the cost of raw material inventory that canmake the company profit by applying this method. The purpose of this research is tohelp apply EOQ method at PT Nindya Beton Salatiga in order to save raw materialinventory cost in production process. This research is a case study research on PTNindya Beton Salatiga by taking secondary data. The data are taken in the form ofgeneral description about the establishment of PT Nindya Beton Salatiga, report onthe purchase of raw materials of 2016 concrete PT Nindya Beton Salatiga, andproduction data of PT Nindya Beton Salatiga. The results of this study indicate thatEOQ method can save raw material inventory cost than traditional method (companypolicy). The cost savings of raw material inventory using EOQ method are as followssand raw material inventory cost savings of Rp 102.059.559,32, raw material of splitstone saving of Rp101.775.993,05,and raw material of cement cost savings of Rp114.387.533,37.Keywords: inventory management, EOQ